Pelatihan Pembelajaran Kolaboratif Jumping Task Berbasis Bahasa Matematis Tapsel Untuk Meningkatkan Kompetensi 6C Abad 21 Siswa SD Negeri 100601 Pintu Padang - Rhamayanti, Yuni; Nida Siregar, Rama; Khomeni, Ayathollah; Hammamah Harahap, Haritsah (PELITA NUSA TENGGARA, 2024)
Collaborative Learning Training of Jumping Task Technique Based on Tapsel Mathematical Language to Improve 21st Century 6C Competencies of Elementary School Students 100601 Pintu Padang. The partners of this community service activity are 22 students of grade V of SD Negeri 100601 Pintu Padang. The partner's problems are as follows: 1) minimal school facilities, 2) students' difficulties in understanding mathematics, 3) low interest in learning mathematics, 4) students' perspectives that consider mathematics as a difficult and boring lesson, 5) low ability and skills of some teachers in presenting teaching materials as interestingly as possible, and 6) limited economic conditions for students to participate in tutoring, 7) Low Competence 6 C, 8) the need to use student language that is based on the experience of the Batak language of Tapsel. To address these issues, we are interested in holding community service activities (PKM) in the field of educational services, namely the Tapsel Mathematical Language-Based Jumping Task Technique Collaborative Learning Training which is considered appropriate for 21st century thinking and is oriented towards students helping students face and solve difficulties in 6C competency questions, namely as facilitators, motivators, innovators, evaluators, as well as educators and mentors in learning simulations discussing 6C competency questions. The method offered to improve 21st century 6C competencies to support the realization of PKM that will be implemented on students is the Tapsel Mathematical Language-Based Jumping Task Technique Collaborative Learning training. Jumping Task is a high-level question or assignment presented using Tapsel mathematical language to develop high-level thinking skills. Meanwhile, the approach used during the implementation of this PKM activity uses a service learning approach aimed at overcoming problems faced by partners and fulfilling practical needs required by students.